Cardiac dysfunction in juvenile dermatomyositis: a case-control study. Issue 5 (7th January 2011) - Schwartz, Thomas; Sanner, Helga; Husebye, Trygve; Flatø, Berit; Sjaastad, Ivar
Abstract : Objective: To compare cardiac function in patients with juvenile dermatomyositis (JDM) with matched controls, and examine associations between pathological electrocardiography (ECG), echocardiographic abnormalities and disease variables in patients with JDM. Methods: A total of 59 patients with JDM, examined a median 16.8 years (range 2–38 years) after disease onset, were compared with 59 age-matched and sex-matched controls. Echocardiography, including early diastolic transmitral flow/early diastolic tissue velocity (E/E') as a marker for diastolic dysfunction, and 12-channel ECG were performed and analysed blinded to patient information. Disease activity and damage were assessed by clinical examination at follow-up and chart review. Results: E/E' was elevated (>9.5) in 13 (22%) patients versus 0 controls (p<0.001). In all, 10 patients presented with pathological ECG compared to 4 controls (p=0.054). Previous or current hypertension was found in 12 patients versus 0 controls (p<0.001). Among the patients, pathological ECG was found in 6/13 patients with versus 4/44 without elevated E/E' (p=0.002); and systolic blood pressure was correspondingly 132±24 mm Hg versus 112±18 mm Hg in the groups (p=0.012). E/E' correlated with cumulative organ damage assessed at follow-up (rsp 0.41, p=0.001) and disease activity at 1 year (rsp 0.56, p<0.001), which also predicted pathological E/E' after controlling for age and gender. During disease course, 12% of patients with JDM developed pericarditis. Conclusion: Only patients with JDM and no controls had subclinical left ventricular diastolic dysfunction; the patients with elevated E/E' also had high prevalence of pathological ECG and hypertension. High disease activity 1-year post diagnosis predicted high E/E' at follow-up. The findings suggest that subclinical heart disease is related to the systemic nature of JDM.